The Influence Of Financial Literacy And Market Orientation On The Performance Of MSMEs - Tasya Virgia; Elsa Meirina (International Journal of Management Research and Economics, 2024)
Recognizing the importance of MSMEs, the government is committed to continuing to encourage and develop MSMEs. Pesisir Selatan Regency is one of 19 districts/cities in West Sumatra that is very aggressively encouraging the revival of MSMEs. The purpose of this study was to examine the effect of financial literacy and market orientation on MSME performance. Quantitative research methods and questionnaires as data collection tools. A total of 88 questionnaires were collected from MSME players in IV Jurai District, the sample calculation used the slovin formula. Data processing using the SPSS application. The results showed that financial literacy has a positive effect while orientation has a negative effect on the performance of MSMEs. In accordance with the formulation of the hypothesis, it is concluded that financial literacy and market orientation affect the performance of MSMEs..